THE EFFECTIVENESS OF AN IMIDACLOPRID-MOXIDECTIN COMBINATION AGAINST NOTOEDRES CATI AND TOXOCARA CATI INFECTIONS IN CATS - Ni Luh Dewi Kustiantari; I Gede Soma; Sri Kayati Widyastuti (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Scabiosis and toxocariosis are diseases commonly found in cats with poor maintenance systems. The purpose of this paper is to determine the treatment of cases of Scabiosis and Toxocariosis in domestic cats by administering spot-on imidacloprid and moxidectin. A domestic cat aged ± 2 years came with complaints of itching, often scratching several parts of its body and experiencing diarrhea. The results of the clinical examination revealed hyperkeratosis, erythema, crusting and alopecia on the cat's face, ears and neck. Based on supporting examination with superficial skin scraping, the presence of Notoedres cati mites and eggs was found. When examining feces using native, sediment and pumice methods, Toxocara cati eggs were found. Based on the history, clinical examination and supporting examinations, the case cat was diagnosed as having scabiosis and toxocariosis with a fausta prognosis. The therapy given is in the form of spot-on administration of a combination of imidacloprid 40 mg and moxidectin 4 mg (Advocate for small cats® <4kg) 1 time in 0.4 mL as causative therapy. Administration of Advocate shows effective results for treating notoedres catii and toxocara catii infestations in one treatment in case cats. Owners are advised to pay attention to sanitation, cleanliness of animals and the surrounding environment to reduce the incidence of infection and parasite infestation. Apart from that, it is best to carry out regular veterinary examinations, including repeating advocate therapy every month as a form of prevention.